Structural and electronic properties of H2, CO, CH4, NO, and NH3 adsorbed onto Al12Si12 nanocages using density functional theory - Li, Liu-Kun; Ma, Yan-Qiu; Li, Kang-Ning; Xie, Wen-Li; Huang, Bin (Frontiers in Chemistry, 2023)
In this study, the adsorption of gases (CH4, CO, H2, NH3 and NO) onto Al12Si12 nanocages was theoretically investigated using density functional theory. For each type of gas molecule, two different adsorption sites above the Al and Si atoms on the cluster surface were explored. We performed geometry optimization on both the pure nanocage and nanocages after gas adsorption and calculated their adsorption energies and electronic properties. The geometric structure of the complexes changed slightly following gas adsorption. We show that these adsorption processes were physical ones and observed that NO adsorbed onto Al12Si12 had the strongest adsorption stability. The Eg (energy band gap) value of the Al12Si12 nanocage was 1.38 eV, indicating that it possesses semiconductor properties. The Eg values of the complexes formed after gas adsorption were all lower than that of the pure nanocage, with the NH3–Si complex showing the greatest decrease in Eg. Additionally, the highest occupied molecular orbital and the lowest unoccupied molecular orbital were analyzed according to Mulliken charge transfer theory. Interaction with various gases was found to remarkably decrease the Eg of the pure nanocage. The electronic properties of the nanocage were strongly affected by interaction with various gases. The Eg value of the complexes decreased due to the electron transfer between the gas molecule and the nanocage. The density of states of the gas adsorption complexes were also analyzed, and the results showed that the Eg of the complexes decreased due to changes in the 3p orbital of the Si atom. This study theoretically devised novel multifunctional nanostructures through the adsorption of various gases onto pure nanocages, and the findings indicate the promise of these structures for use in electronic devices.